The influence of instructional leadership on learning motivation and student activity - Afriza Afriza; Syafaruddin Syafaruddin; Nurhasnawati Nurhasnawati; Khairina Khairina; A. Munir (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
In the context of acquiring foreign language competence, motivation plays an important role in determining the outcome of the learning process. This study explores the influence of instructional leadership on the motivation and learning activity of students in language learning at the Tanjung Berulak Islamic Madrasah Tarbiyah Pondok Pesantren (PPMTI). The study uses a quantitative correlational approach, with a population of as many as 620 students from PPMTI Tg. Berulak. The sample size of 71 respondents was determined using proportionate stratified random sampling. Data analysis includes validity testing of research instruments and regression analysis to measure the impact of instructional leadership on student motivation. The regression analysis resulted in a coefficient of 0.870, which indicates that the improvement in instructional leadership by one unit was linked to the increase in student motivation by 0.870. In addition, the study also found that motivation significantly affects student learning activity, with a significance rate counted below 0.05. The findings highlight the important role of instructional leadership in enhancing the motivation and active participation of students in language learning environments.